Editorial [Hot Topic: Pain - Unmet Need and Emerging Targets & Therapies (Guest Editor: Sivaram Pillarisetti)] - Pillarisetti, Sivaram (CNS & Neurological Disorders - Drug Targets, 2011)
Patients with persistent pain present a problem for all clinicians [1, 2]. The International Association for the Study of Pain defines pain as “an unpleasant sensory and emotional experience associated with actual or potential tissue damage, or described by the patient in terms of such damage. Although it is generally conceived that pain is always associated with a pathological lesion, the problem with most patients is that the pathology is not easily found. In diseases such as rheumatoid arthritis treating the underlying disease with disease modifying agents (e.g. methotrexate or anti-tumor necrosis factor-α (TNFα) therapies) will in most cases address the joint pain associated with rheumatoid arthritis. Not all inflammatory pain states can be treated with such therapies and most non-inflammatory pains (e.g. neuropathy, cancer pain) has either no clear underlying disease state or the treatment itself can induce pain-causing pathology (e.g. chemotherapy-induced pain). Persistent pain associated with injury or diseases (such as diabetes, arthritis, or cancer) can result from damage to nerve fibers, leading to increased conduction or neurotransmitters. The reader is referred to recent reviews on molecular mechanisms of pain in general or specific pain types [3-5] There are at least three main classes of drugs used to treat pain: 1) the non-steroidal anti-inflammatory drugs (NSAIDs or coxibs) - examples include naproxen, diclofenec and celecoxib - generally for mild-to-moderate inflammatory pain; 2) narcotic analgesics - examples include morphine, oxycodone and buprenorphine - for moderate-to-severe pain including cancer pain and neuropathic pain; and 3) the non-traditional analgesics (antidepressants and anticonvulsants) - mainly for neuropathic pain. Inflammatory nociceptive pain is associated with inflammation and tissue damage. Cytokines (TNFα, interleukins 1 and 6) are often elevated resulting in accumulation of inflammatory cells. Cyclooxygenase (COX), an enzyme required for the synthesis of prostaglandins, is elevated in response to cytokines [5]. Prostaglandins produced by COX cause inflammation and pain. All NSAIDs exhibit a similar mechanism of action, i.e., COX activity. Although effective on mild-to-moderate pain, gastrointestinal (GI) ulcerations are the major problem with traditional NSAIDs that inhibit both COX-1 and COX-2 [6]. Although COX-2 inhibitors offer a better GI safety profile, between 2004 and 2005 two of the available COX-2 inhibitors, rofecoxib (Vioxx, Merck & Co) and valdecoxib (Bextra, Pfizer) were withdrawn from the market due to an increased risk of adverse cardiovascular events [7]. Celecoxib (Celebrex, Pfizer) is still available for use, but should be used with extreme caution in patients with existing cardiovascular (CV) disease. Currently aspirin and naproxen are the only NSAIDs that are either CV protective (aspirin) or with minimal adverse CV effects (naproxen). Naproxen is a relatively more potent analgesic; however, both drugs suffer from serious GI issues. Several companies are working on improving the GI/CV profile of naproxen and other drugs. NiCox is developing a nitric oxide donating version of naproxen (Naproxcinod) for pain associated with osteoarthritis. Although it appears to have some hypotensive effect [8], its overall CV benefits remain to be proven, and it was recently rejected by the FDA panel. Logical Therapeutics is developing its investigational drug LT-NS001 (naproxen etemesil, in Phase 2), which is pharmacologically inactive in the GI tract, but once absorbed into the bloodstream is converted to naproxen. Opioids are the most commonly prescribed and perhaps most effective medications for pain. It is estimated that 90% of patients presenting to pain centers and receiving treatment in those facilities are on opioids [9, 10]. Opioids can be considered broad-spectrum analgesics that act at multiple points along the pain pathway. Opioids, which are generally prescribed for moderate-to-severe pain (cancer/non-cancer pain, back pain and breakthrough pain), are agonists, mixed agonists-antagonists, or partial agonists for opioid receptors [11-13]. Opioids achieve their analgesia through their interaction primarily with the mu and kappa opioid receptors. There is some evidence that these agents also act at delta opioid receptors. The mu receptor has been identified in the neural tissue of areas that are part of the body's descending pain pathway. Opioids' activity at these receptors also mediates their adverse effects i.e., euphoria, respiratory depression and constipation [10]. The kappa receptor mediates sedation. The delta receptor mediates dysphoria and psychomimetic effects. Other common adverse effects of opioid use include urinary retention, orthostatic hypotension, nausea and vomiting. Another major issue often encountered with long-term use of opioid therapy is the development of tolerance - defined as the failure of a steady dose of the drug to sustain the desired pharmacological effect over time, i.e., the need to increase drug dose to maintain the desired pharmacological effect. Opioid use in neuropathic pain is often limited by the development of analgesic tolerance. In addition, sustained use sometimes leads to the development of hyperalgesia - dramatically increased sensitivity to painful stimuli. Inflammation and inflammatory cytokines appear to be key players contributing to the development of tolerance and hyperalgesia [14]..........